2011
DOI: 10.1038/bjc.2011.6
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I clinical study of cisplatin-incorporated polymeric micelles (NC-6004) in patients with solid tumours

Abstract: Background:On the basis of preclinical studies of NC-6004, a cisplatin-incorporated micellar formulation, we hypothesised that NC-6004 could show lower toxicity than cisplatin and show greater anti-tumour activity in phase I study.Methods:A total of 17 patients were recruited in a range of advanced solid tumour types. NC-6004 was administered intravenously (i.v.) every 3 weeks. The dose escalation started at 10 mg m−2 and was increased up to 120 mg m−2 according to the accelerated titration method and modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
209
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(210 citation statements)
references
References 13 publications
1
209
0
Order By: Relevance
“…These characteristics suggest that at the maximum-tolerated dose (MTD) of NC-6004, antitumor activity may be greater than that of cisplatin. In addition, the ultrafiltrate platinum C max of NC-6004 was 34-fold lower than ultrafiltrate levels of cisplatin at therapeutic doses (20). The lower C max is potentially a clinically significant characteristic, particularly in patients with poor renal function as high ultrafiltrate platinum C max levels (!400 mg/mL) are associated with nephrotoxicity and a decline in creatinine clearance (21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These characteristics suggest that at the maximum-tolerated dose (MTD) of NC-6004, antitumor activity may be greater than that of cisplatin. In addition, the ultrafiltrate platinum C max of NC-6004 was 34-fold lower than ultrafiltrate levels of cisplatin at therapeutic doses (20). The lower C max is potentially a clinically significant characteristic, particularly in patients with poor renal function as high ultrafiltrate platinum C max levels (!400 mg/mL) are associated with nephrotoxicity and a decline in creatinine clearance (21).…”
Section: Introductionmentioning
confidence: 99%
“…The results from the previous phase I trial of single agent NC-6004 in patients with solid tumors suggested acceptable tolerability and dose-proportional activity in the treatment of advanced solid tumors and defined a recommended dose of 90 mg/m 2 (20). Following this trial, a phase I/II trial in Asia was started in patients with metastatic pancreatic cancer evaluating escalating doses of NC-6004 in combination with gemcitabine using a traditional 3þ3 modified Fibonacci dose escalation design.…”
Section: Introductionmentioning
confidence: 99%
“…(Nanoplain: PEG + poly-glutamic acid) [18,361] and NK012 (PEG + poly-glycolic acid) [18,362], containing cisplatin or SN38, respectively, and the phase II/III trials of the P-glycoproteintargeting pluronic micelle of doxorubicin (SP1049C) that was labeled as orphan drug by the FDA in 2008 [347,354].…”
Section: Polymeric Nanocarriersmentioning
confidence: 99%
“…25,26 Ongoing clinical evaluations of several candidate nanoformulations in conjugation with a wide range of chemotherapeutic or immunotherapeutic payloads are a testament of the efficacy of nanoparticle-based drug delivery approaches. 27,28 For example, Nanoplatin NC-6004, a cisplatin containing polymeric nanocarrier is under Phase I/ II clinical trial, 29 whereas cyclodextrin-based nanoparticles CALAA-01 that delivers small-interfering RNA (siRNA) agent to shut down a key enzyme (ribonucleotide reductase) in cancer cells is under Phase I evaluation. 30 Similarly, an engineered adenovirus nanoparticle-based drug delivery platform is under Phase-1 dose escalation study for delivery of cancer immunotherapy to patients with chronic lymphocytic leukemia (CLL) 31 while the pH sensitive polymeric nanoparticle CRLX101 loaded with camptothecin is undergoing Phase II clinical trials.…”
Section: Introductionmentioning
confidence: 99%